2018- CSA Monitoring: Hoima Climate-Smart Village (Uganda) - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Jarvis, Andrew; Recha, John W.M.; Ambaw, Gebermedihin; Kakeeto, Ronald (2019)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Hoima Climate Smart Village (Uganda) in October 2018. This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: